2020
DOI: 10.31925/farmacia.2020.4.4
|View full text |Cite
|
Sign up to set email alerts
|

A Follow-Up Study of the Occupational Hand Eczema and Skin Damage Risk in Healthcare Providers From Romania in Time of Covid-19

Abstract: The aim of this work was to estimate the prevalence and risk factors of self-reported, work-related occupational hand eczema, targeting personnel working in hospitals and ambulatory units throughout Romania. A standardized questionnaire was specifically addressed to healthcare professionals from different medical fields. Out of 245 healthcare providers who took part in the survey, 161 (65.71%) were nurses, and 235 (95.92) women, which confirms that women are prevalent in this working sector. The latex powder-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Previous studies have looked at the link between COPD, depression and IL-6 and found that there are changes at the molecular level. As IL-6 is released through kynurenine, which is involved in serotonin homeostasis, systemic inflammation and depression, there is an increase in IL-6 and a low level of serotonin [67]. Both in COPD and depression, IFN-ɤ and IL-2 were found to be involved in the inflammatory process.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Previous studies have looked at the link between COPD, depression and IL-6 and found that there are changes at the molecular level. As IL-6 is released through kynurenine, which is involved in serotonin homeostasis, systemic inflammation and depression, there is an increase in IL-6 and a low level of serotonin [67]. Both in COPD and depression, IFN-ɤ and IL-2 were found to be involved in the inflammatory process.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Handwashing alone is not the only contributor, as further data from China reported the detrimental role played by N95 masks [5]. Also, a study published by Chiriac et al established that Cd and Ca detected on the inner surface of powder free latex gloves used by healthcare professionals contributed to the toxicity to the skin that led to work-related occupational hand eczema [6]. Seeing the striking increase in the number of ICD cases during the challenging COVID-19 pandemic (March -May 2020), we decided to assess the efficacy of a new barrier cream designed to isolate and repair damaged skin following exposure to the aggressive action of external irritative substances, allergens, particulate pollutants.…”
Section: Introductionmentioning
confidence: 99%